PENGGUNAAN PENDEKATAN KONSELING BEHAVIORISTIK DENGAN TEKNIK CINEMA THERAPY UNTUK MENGATASI PROKRASTINASI AKADEMIK SISWA KELAS XI DI SMA SWASTA DHARMAWANGSA - Purbatua Manurung; Ira Suryani; Alysha Putri Nabilla (Al-Irsyad: Jurnal Pendidikan dan Konseling, 2019)
Behavioristic Counseling is counseling offered by human behavior, also most of the students in the school. The purpose of behavioral counseling is to change behavior in accordance with the environment, by providing with therapy to students, then students will take the value related to the film, so that the value of film therapy can change the direction of Academic Procrastination to applied to students to be successful. The type ofresearch used is Qualitative. The sample drawing in this research are 11th grade of SMA swasta dharmawangsa. The technic of data accumulation is Interview, observation, and documentation. And then , technic data analysis is data reduction, data serving, and attract the conclusion. The result of research indicates all the positive things. that's alteration of student behavior which is used to delay those homework turns out to be the student who prepare those homework in no time. All the task that teachers gives can be prepared well. The things indicates that behavioristic counseling approach by using cinema therapy technic can solve academic procrastination that happens with students of SMA swasta Dharmawangsa Medan.Keyword: Behaviouristic Counseling, Cinema Therapy, Academic Procrastination